Inhibition of YB-1 phosphorylation enhances cisplatin activity and disrupts cell division in pleural mesothelioma - Schelch, Karin; Maach, Nadine; Hashim, Muhammad; Zitta, Benjamin; Kirchhofer, Dominik; Timelthaler, Gerald; Solta, Anna; Emminger, Dominik; Kopatz, Verena; Hoda, Mir A.; Berger, Walter; Aigner, Clemens; et al. (British Journal of Cancer, 2025)
Background: The cold-shock domain protein YB-1 is overexpressed in pleural mesothelioma (PM) and was shown to contribute to increased cell migration and platinum resistance. Methods: Phosphorylation of YB-1 at position serine 102 was analysed by immunohistochemistry, immunofluorescence and immunoblotting in PM tissue specimens and cell lines. Intracellular localisation experiments involved immunoblotting, transfection of fluorescent protein-tagged YB-1 and confocal imaging. YB-1 phosphorylation was inhibited with the RSK inhibitors BI-D1870 and LJH685. Effects of inhibition alone and in combination with radiation or cisplatin treatment were analysed by cell viability assays, clonogenic assays and videomicroscopy-based migration and cell fate map analyses. Results: YB-1 phosphorylated at serine 102 is present in PM cell lines and tissue. Inhibition of phosphorylation with BI-D1870 reduced YB-1 localisation in the cell nucleus and led to reduced cell viability, clonogenicity, migration and disrupted cell division. Moreover, exposure to BI-D1870 increased the effect of radiation and cisplatin treatment with additive to synergistic effects in PM cell lines and primary cultures. Conclusions: The serine 102 phosphorylated form of YB-1 contributes to the malignant phenotype of PM. Inhibition of YB-1 phosphorylation warrants further exploration as part of treatment strategies for this devastating disease.